Hepcidin and iron: novel findings for elite female rugby sevens players - Smith, S.; Sims, S. T.; Thorpe, H.; Baker, D.; Haszard, J.; Badenhorst, C.; Black, K. E. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: Iron deficiency is a common deficiency disease worldwide with athletes at increased risk. METHODS: A proposed new mechanism of exercise-induced iron deficiency in athletes involves the iron-regulatory hormone hepcidin, however, there is limited information on this amongst elite athletes. This study describes iron status in elite female rugby Sevens players. RESULTS: Blood samples were collected at the start and mid-season and analyzed for serum iron, serum ferritin (SF), soluble transferring receptor (sTfR), high sensitivity C-reactive Protein (hsCRP) and hepcidin. Of the 17 players 18% were iron deficient (SF<30 µg/L) with 29-35% of players with sub-optimal iron stores at some point during the study (SF<45 µg/L). Serum hepcidin was strongly correlated with SF (r=0.61, P=0.0001). CONCLUSIONS: Some elite female rugby Sevens players have sub-optimal iron stores over the course of a season.